EFFECTS OF MICROORGANISMS AND BIODIESEL CONCENTRATION ON CARBON STEEL STORAGE TANKSâ CORROSION BY - Metanoia Pusparizkita, Yustina
EFFECTS OF MICROORGANISMS AND BIODIESEL CONCENTRATION ON CARBON STEEL STORAGE TANKS’ CORROSION By Yustina Metanoia Pusparizkita NIM: 33017001 (Doctoral Program in Chemical Engineering) Fossil or biofuel is generally stored in storage tanks. Most hydrocarbon storage tanks are made of carbon steel because of its high strength, formability, and lower cost. However, carbon steel is easily corroded chemically or due to the influence of the presence of microorganisms in hydrocarbon fuels (biocorrosion). In this case, the use of biodiesel as a mixture of diesel oil, has the potential to increase corrosion in hydrocarbon storage tanks. In this case, the use of biodiesel as a mixture of diesel oil has the potential to increase corrosion in hydrocarbon storage tanks. At present, in Indonesia, the use of biodiesel as a mixture of diesel oil has a higher concentration than that of the mixture found in other countries, which reaches 30% v/v. With a relatively high mix ratio, hygroscopic biodiesel tends to be more easily contaminated with the presence of microorganisms and easily degraded. On the other hand, biodiesel blends can be utilized by microorganisms as a source of carbon to carry out metabolism that will form biofilms and induce the corrosion process. Of the many species, Bacillus sp. is known as a microorganism that dominates the biodegradation of hydrocarbon products, and it can affect the rate of corrosion. Bacillus activity is proven to increase the rate of metal corrosion, especially when there is an increase in the concentration of biodiesel in a mixture with diesel oil. The activity of these microorganisms will form corrosion products in the form of iron oxide and result in pitting corrosion damage. Thus, the use of biodiesel as a mixture of diesel oil, especially the mechanism of microorganisms influencing on the rate of corrosion, the resulting metabolites, and their effects on the level of damage to pitting corrosion needs to be further investigated. Also, the types of microorganisms that can affect corrosion in biodiesel and diesel mixture storage systems in Indonesia have not been identified to date. Therefore, this research was carried out in the process of isolation. Subsequently, the contribution of local microorganisms was studied to find out the biocorrosion problems to be faced, especially in biodiesel and diesel mixture storage tanks. In this study, the phenomenon of biocorrosion in the tank was observed by simulating storage through carbon steel immersion in the mixture of biodiesel and vi diesel oil medium. In the early stages of this study, Bacillus megaterium was used as a contaminating microorganism model (selection of microorganisms based on literature studies). The growth was analyzed by the TPC, while the production activities of EPS and acid metabolites, and their effects on corrosion were reviewed based on analyzes using SEM, acidimetric titration, gravimetry and impedance. Corrosion damage caused by pitting was evaluated qualitatively and quantitatively by observation and measurement using a digital microscope. The identification process of local microorganisms was carried out by taking carbon steel corrosion products that had been immersed in diesel oil for two months and were then selected based on the speed of growth and species analyzed by PCR 16S.rRNA. The results of the experiment showed that one type of microorganism identified from the corrosion products formed in the diesel oil in Indonesia was Bacillus licheniformis. The literature study conducted shows that this species can form biofilms and affect corrosion. Specifically, the effect of activity on biocorrosion for both Bacillus megaterium species used as model microorganisms and Bacillus licheniformis was evaluated based on TPC and gravimetric analysis. The formation of biofilm was proven by SEM results, while biodiesel degradation was analyzed using GC-MS. The impact of corrosion from Bacillus licheniformis activity was also observed, measured with a digital microscope, and the corrosion products formed were analyzed by the XRD method. The results showed that corrosion occurred in the storage system was not entirely influenced by microorganisms. Electrochemical corrosion between metals and the medium also played a role. However, in general, the presence of microorganisms increased the rate of corrosion of carbon steel compared to sterile conditions. The biodiesel concentration influenced the growth and formation of biofilms of both species on the surface of carbon steel. The higher the concentration of biodiesel in the medium, the higher the average growth of microorganisms increased. During growth, microorganisms produced EPS as a constituent of biofilms and also acid metabolites that can affect corrosion. However, based on experiments using Bacillus megaterium, the acidic conditions created under biofilm have less effect on corrosion compared to the non-uniform surface conditions of metals due to biofilm formation. As biodiesel concentrations increased, the presence of Bacillus megaterium accelerated the corrosion rate of carbon steel, while Bacillus licheniformis activity actually slowed it down. This is due to Bacillus licheniformis producing metabolite compounds that act as corrosion inhibitors. Besides affecting the growth of microorganisms and the corrosion rate of carbon steel, an increase in the concentration of biodiesel also influenced the damage to pitting corrosion. Wide, shallow pitting was formed when microorganisms obtained sufficient carbon sources, and biofilms tend to cover the metal surface evenly. Widespread damage is similar to uniform corrosion and an increase in metal surface roughness. This result makes it easier to detect corrosion damage and evaluate the feasibility and life of the tank. Still, corrosion has an impact on tank life. In general, although the tank has been manufactured according to applicable standards, corrosion will shorten its lifespan vii when compared to non-corrosive tanks. However, the occurrence of corrosion is unavoidable. Besides easier to detect, the life of storage tanks can last longer if the form of corrosion is wide and shallow pitting compared to that with the small and deep pits. Thus, deep pitting corrosion must be highly avoided because this corrosion can have an impact on unexpected storage tank leakage and unpredictable tank life. Keywords: biocorrosion, steel, biofilm, Bacillus, hydrocarbons, pitting